Cross-cultural adaptation of the physician orders for life-sustaining treatment form to Brazil - Mayoral, Vania F.S. [UNESP]; Fukushima, Fernanda B. [UNESP]; Rodrigues, Aniela M. [UNESP]; Carvalho, Raissa P. [UNESP]; Carvalho, Larissa P. [UNESP]; Pinheiro, Leandro A.F.V.; Polegato, Bertha F. [UNESP]; Minicucci, Marcos F. [UNESP]; Bassett, Rick; Moss, Alvin H.; Steinberg, Karl E.; Vidal, Edison I.O. [UNESP] (SAGE Publications, 2018)
Background: The Physician Orders for Life-Sustaining Treatment (POLST) paradigm is considered one of the most important strategies to respect patients' values at the end of life in the United States. The cross-cultural adaptation of POLST entailed several methodological considerations, which may be informative for international researchers who may also consider bringing POLST to their countries as a means to promote care at the end of life that is consistent with patients' preferences. Objective: To report the methods and outcome of the cross-cultural adaptation of the POLST form to Brazil. Design: Cross-cultural adaptation study. Setting/Subjects: Twenty physicians and 10 patients at a university hospital participated in the pilot tests. Results: The cross-cultural adaptation process included choosing which existing POLST form(s) to use as a source, deciding the intended reading level, which healthcare professionals should be allowed to sign the form, and consultation with attorneys, bioethicists, and members of the National POLST Paradigm Task Force. Pilot tests occurred in two stages using different approaches. First, 20 physicians were trained about POLST and asked for any unclear aspects related to the form. Second, trained investigators completed POLST forms after engaging in advance care planning conversations with 10 hospitalized patients or patients' surrogates. Conclusions: This report provides a basis for future cross-cultural adaptations of POLST to other countries. The authors hope such new adaptations will broaden the possibilities of research using POLST and also may promote wider provision of care at the end of life that is consistent with patients' preferences.
Keywords: advance care planning; advance directives; Brazil; cross-cultural adaptation studies; palliative care; polst